Isolation and identification of the human pathogen Pythium insidiosum from environmental samples collected in Thai agricultural areas - Supabandhu J. (2014)
We describe the ecological niche of the human and animal pathogen Pythium insidiosum within endemic agricultural areas of Thailand. Samples were collected from irrigation water, including rice paddy fields, irrigation channels and reservoirs. Zoospores of P. insidiosum were captured from water by the use of a sterile human hair baiting technique. Pythium isolates were identified based on phenotypic characteristics and by using a specific PCR assay for P. insidiosum. In addition, internal transcribed spacer (ITS) regions of P. insidiosum rDNA were sequenced and used in the phylogenetic analysis of 20 other known P. insidiosum DNA sequences available in the database and 11 related DNA sequences of other Pythium species including Lagenidium giganteum. The sequences of 59 environmental isolates of Pythium spp. recovered from Thailand confirmed 99% identity to P. insidiosum. Three well supported phylogenetic groups within P. insidiosum were found. The protein profiles of P. insidiosum environmental strains were determined and compared with reference strains. A typical 45-30 kDa band was consistently found in all isolates of P. insidiosum but not in closely related Pythium species. This study provides the first evidence for the natural occurrence of P. insidiosum in endemic aquatic environments. The highest recovery rate of this hydrophilic pathogen was found to be from water reservoirs and our data show that irrigation water may be an important source of P. insidiosum infection for individuals working in endemic agricultural areas.